Assessment of Instructional Labor Support Behaviors among Laboring Women at Teaching Hospitals in Hilla City - Khairi, suhad; Mukeef, suad (Iraqi National Journal of Nursing Specialties, 2015)
Objectives: The aim of this study to assess instructional labor support behaviors among laboring women in teaching hospitals in Hilla city. Methodology: A descriptive analytic study was concluded to select a sample purposely of one hundred multipara laboring women in maternity hospital in Hilla city and data was collected through questionnaire form during February (1 st to March 30th) 2014. A descriptive statistical method was used to analyze the data. Results: The result showed that the highest percentage of study sample was at age (20-24) years, most of them was house wife, more than third graduate from primary school, and more than half of them lived in rural area, (86%) of study sample delivered normal delivery, and (47%) of them their babies were healthy, regarding instructional labor support behaviors, the highest mean of score refer to instruction with eye to eye contact with persons who provide support, use open mouth (glottis) pushing and follow urges to push and rise the baby to let mother see her baby’s gender. Recommendations: The result of this study indicated need for providing all midwifery school with labor support behaviors, revising clinical guideline and efficient updating training to all staff and give role to family to share in labor support behaviors